2022
DOI: 10.1136/bmjopen-2021-057353
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of progesterone supplementation in women presenting low progesterone levels on the day of frozen embryo transfer: a randomised controlled trial

Abstract: IntroductionProgesterone is an essential hormone involved in the process of implantation and pregnancy maintenance. Evidence from recent studies has supported the importance of serum progesterone level around the time of embryo transfer in hormonal replacement therapy frozen embryo transfer cycles and recommended the need for individualised luteal support. Low progesterone around the time of embryo transfer is found to be associated with decreased rate of pregnancy after frozen embryo transfer. This single-cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…E2 first causes hyperplasia and hypertrophy of endometrial epithelial cells (9), but its role in the luteal phase is unclear (8). Although the role of E2 in the coordination and implantation of blastocyst is not clear, the role of P4 in the luteal phase is better defined, and it has been shown that lumpectomy before the seventh week of pregnancy leads to abortion in most cases (10). P4 causes the endometrium prepared with E2 to become secreted tissue and provides an environment ready for ET to uterine tissue (11).…”
Section: Introductionmentioning
confidence: 99%
“…E2 first causes hyperplasia and hypertrophy of endometrial epithelial cells (9), but its role in the luteal phase is unclear (8). Although the role of E2 in the coordination and implantation of blastocyst is not clear, the role of P4 in the luteal phase is better defined, and it has been shown that lumpectomy before the seventh week of pregnancy leads to abortion in most cases (10). P4 causes the endometrium prepared with E2 to become secreted tissue and provides an environment ready for ET to uterine tissue (11).…”
Section: Introductionmentioning
confidence: 99%